Can Stroboscopic Training Improve Time-to-Collision Judgments of Laterally Moving Objects?. (September 2018) - Braly, Adam M.; DeLucia, Patricia R.
We investigated whether effects of stroboscopic training on time-to-collision (TTC) judgments depend on the optical flow pattern. Prior research showed that TTC judgments of lateral motion reflected benefits of stroboscopic viewing (Ballester, Huertas, Uji, & Bennett, 2017; Smith & Mitroff, 2012), but TTC judgments of approach motion did not reflect such benefits (Braly & DeLucia, 2017). This discrepancy may be due to differences in the optical flow patterns between lateral and approach motion. In lateral motion, the optical flow pattern is linear; the change in the object's optical position is the same throughout its trajectory. In approach motion, the optical flow pattern is non-linear; the change in the object's optical size increases as it gets closer to the eye. It has been proposed that this difference in the optical flow pattern underlies the greater accuracy of TTC judgments that occur with lateral motion compared to approach motion (Schiff & Oldak, 1990). In the current study, we measured effects of stroboscopic viewing on TTC judgments of lateral motion using identical methods in our prior study of approach motion. Although prior research demonstrated potential benefits of stroboscopic viewing for judgments of lateral motion, the stimulus was visible when the response was made. Prior demonstrations that the object's trajectory (and thus nature of the optic flow) affects TTC judgments were demonstrated with prediction-motion (PM) tasks in which the object disappeared before a response was made. The two types of tasks are putatively based on different visual information and cognitive processes (Tresilian, 1995). Thus, we used a PM task in the current study. Participants viewed computer simulations of an object that moved laterally toward a target and then disappeared. They pressed a mouse button at the exact time that they thought the object would hit the target. Mean constant error and variable error of TTC judgments were compared among intervention conditions of stroboscopic training (5 minutes in duration), continuous viewing (practice without feedback), and a control filler task. Performance was measured during four sessions—pre-test, intervention, immediately after intervention, and 10 minutes after intervention. When distance was far, participants in the stroboscopic intervention condition were, on average, less variable at the 10-minute posttest compared to the pretest. Although the difference was not statistically significant, it is noteworthy that performance did not significantly degrade over time as it did in the filler condition, and in our prior study of approach motion (Braly & DeLucia, 2017). Such results suggest that stroboscopic training can protect against performance degradation over time (due to fatigue, monotony, etc). A protective effect also was observed in the continuous vision condition (performance did not degrade over time); however, observations of the means suggest that performance would have degraded over time if longer training was completed. When TTC was 3.0 s, performance in the stroboscopic intervention was not more variable in the immediate posttest compared to the pretest and, more importantly, was less variable at the ten-minute posttest (although p = 0.0515). Our results show that under specific conditions (when TTC was 3.0 s; when distance was far) stroboscopic training can protect against performance degradation over time; that is, variable error did not increase. Such protective effects of stroboscopic training were not observed in our earlier study of approach motion (Braly & DeLucia, 2017). Neither study showed a significant effect of stroboscopic training on constant error. The implication is that the effects of stroboscopic training depend on the nature of the optical flow pattern. In future studies, it is important to systematically determine the conditions under which stroboscopic training can improve performance. Results will have important implications for traffic safety and for driver training programs.